Metabólitos secundários de Eriotheca pubescens (Malvaceae): atividades antioxidante e inibitória de catepsinas - (:unkn) unknown (Universidade Federal de Goiás, 2015)
In the present work the chemical study of Eriotheca pubescens lead to the isolation and structural identification of secondary metabolites present in the stems and leaves of this species. Furthermore, it was evaluated of antioxidant potential by the capture method of free radicals using DPPH and the study also was lead to search cathepsins K, L, and V inhibitors through in vitro test using the fluorogenic substrate Z-FR-MCA. The chemical study of the ethanolic extract from the stem led to the isolation and identification of triterpenoids α-amyrin and β-amyrin; two diterpenoids, 7-oxo-labda-8,13-dien-15-oic acid and ent-Δ13,14- labd-8β-ol-15-oic acid; four derivatives of benzoic acid, p-hydroxybenzoic acid, 3,4-dihydroxybenzoic acid, 4-hydroxy-3,5-dimethoxybenzoic acid, 3-methoxy-4- hydroxybenzoic acid and flavonoid quercetin. From the ethanolic extract of the leaves, it has been isolated and identified two triterpenoids, lupenona and lupeol. The compounds 3,4-dihydroxybenzoic acid (EC50 0,34 ± 0,0083 mM) and quercetina (EC50 de 0,11 ± 0,0057 mM) showed high antioxidant potential using DPPH assays. The extracts and the major fractions showed above 50% inhibitory activity against cathepsins K, L and V. The p-hydroxybenzoic acid was shown to be a moderate inhibitor (IC50 135,81 ± 17,07 μM) and quercetin a potent and selective inhibitor (IC50 2,2 ± 0,2 μM), both against cathepsin V. These results are important to contribute the chemical and biological knowledge of this species, which so far has no reports of chemical and biological studies.
Secundary metabolites of Eriotheca pubescens (Malvaceae) antioxidant activities and cathepsins inhibitory
Keywords: Eriotheca pubescens; Metabólitos secundários; Antioxidante; Enzimático; Eriotheca pubescens; Secundary metabolites; Antioxidant; Enzymatic; CIENCIAS EXATAS E DA TERRA::QUIMICA